Effects of resistance and balance exercises for athletic ability and quality of life in people with osteoporotic vertebral fracture: Systematic review and meta-analysis of randomized control trials - Li, Xuefei; Chen, Wenhua; Chen, Qian; Li, Fangfang; Chen, Chen; Li, Pan; Li, Fangyu; Guo, Suxia; Chen, Pinghua; Yuan, Weina; Liu, Dan; Wang, Shiyun; et al. (Frontiers in Medicine, 2023)
Purpose This study aimed to use meta-analysis to determine the impact of resistance and balance training on athletic ability and quality of life for patients with osteoporotic vertebral fracture (OVF). Methods This study followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) criteria for systematic reviews and meta-analyzes. The PubMed, Web of science, Cochrane, Embase, and CNKI databases were searched for randomized controlled trials (RCTs) up to September 2022. The search strategy was related to the intervention measures, population, and results, and was structured around the search terms: “Exercise,” “Osteoporotic vertebral fracture,” and “activities of function.” Two reviewers strictly implemented the inclusion and exclusion criteria. Subgroup analyzes of age and training duration were performed for the main outcomes. Results We included 12 RCTs (n = 1,289) of resistance and balance training in patients with OVF. Compared with controls, the intervention group showed improvements on the Quality of Life Questionnaire issued by the European Foundation for Osteoporosis, visual analog pain scale, Timed Up and Go, falls efficacy scale international (FES-I), kyphosis, and functional reach. On subgroup analysis, the effect was more significant when training continued >10 weeks. Conclusion Resistance and balance exercise training improved function and balance, and reduced fall risk in patients with OVF. We recommend resistance and balance training for at least 10 weeks. Future multicenter, large sample trials are needed for more reliable conclusions.